Rabbit hole : a novel - Brody, Kate (Soho Crime, 2024)
"Ten years ago, Theodora "Teddy" Angstrom's older sister, Angie, disappeared. Her case remains unsolved. Now-on the anniversary of Angie's disappearance-Teddy's father, Mark, has killed himself. Unbeknownst to Mark's family, he had been actively investigating conspiracy theories sourced from a Reddit community of true crime fans fixated on Angie, and Teddy soon finds herself falling down that same rabbit hole. After all, if hope dies last, Angie could still be alive. Teddy's burgeoning investigation quickly gets her in hot water with everyone from her frustrated colleagues at the pretentious high school where she teaches English to her middle-aged gun nut boyfriend and her long-lost half-brother. Further complicating matters is Teddy's growing obsession with Mickey, a charming amateur sleuth from Reddit who is eerily keen on helping Teddy solve the case. Bewitched by Mickey, Teddy begins losing her grip on morality. As she struggles to reconcile new information with old memories, her erratic behavior reaches a fever pitch, but she won't stop until she finds Angie-or destroys herself in the process. In Rabbit Hole, debut author Kate Brody has crafted a biting critique of the Internet's voyeuristic boundary trampling, an equally outrageous and heart-wrenching character study of a mind twisted by grief, and a page-turning mystery that's as addictive as a late-night Reddit binge."--